Luminescence-based methods for cellular guanosine triphosphate (GTP) - Yli-Hollo, Titta (My University, 2023)
Guanosine triphosphate (GTP) is an important energy and signaling molecule. The cellular concentration of GTP increases in rapidly dividing cells, such as cancer cells, since GTP is needed in the translation of proteins. In cancer cells, GTP concentration in relation to adenosine triphosphate (ATP) increases significantly. Inosine-monophosphate dehydrogenases (IMPDH) are responsible for the synthesis of GTP and have attracted attention as a potential drug target, among other potential GTP sensor proteins. Thus, new techniques to study GTP and its cellular regulation would benefit the investigation of new drug targets and the development of cancer drugs. To investigate GTP, efficient binders would be beneficial, and previously, our group has successfully developed the first fragment antigen-binding (Fab) against GTP using the phage display technology. The introduced Fab2A4 has over 100-fold specificity to GTP over other purine nucleotide ATP and guanosine diphosphate (GDP). Using this antibody, a competitive assay utilizing GTP-conjugated 9-dentate Eu3+-chelate has been developed for the analysis of GTP hydrolysis. In bioimaging, cellular GTP has been imaged indirectly utilizing various GTP sensors in the past. Small molecules, such as nucleotides, are difficult targets for imaging from fixed cells and require specific binders with high affinity. Additionally, the high intracellular ATP concentration sets high demands for GTP binder specificity. In this study, the aim was to develop new methods to monitor GTP concentrations utilizing GTP-specific antibody. Two cell-based applications were developed by using the anti-GTP Fab. Firstly, the method was developed for direct GTP imaging from fixed cells with fluorescence microscopy. In bioimaging, the new maturated GTP antibody variant Fab2A4m showed improved functionality in comparison to Fab2A4. Secondly, Fab2A4 was utilized in a time-resolved luminescence-based (TRL) homogenous assay with 9-dentate Eu3+-chelate for GTP and combined with ATP detection from cell lysate. The long-lived emission of lanthanide chelates enables the TRL measurements, and therefore the background autofluorescence can be eliminated, leading to high assay sensitivity. In two cell strains, both methods were used to compare cellular GTP levels after different treatments, and for imaging also the expression of GTP synthetic IMPDH2 enzyme.
Keywords: guanosine triphosphate, immunofluorescence, luminescence, lanthanide chelates